A MOORA-Based Decision Support Framework for Ranking Healthcare Service Performance Using Patient Perception Data - Samuel Manurung; Indra M Sarkis; Mufria J Purba; Gortap Lumbantoruan (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2026)
Healthcare service performance evaluation has become an essential aspect in improving service quality and supporting evidence-based decision-making in healthcare institutions. Increasing patient expectations require healthcare providers to assess and enhance their service performance across multiple dimensions continuously. Therefore, a systematic, objective evaluation approach is needed to measure service quality effectively. This study aims to evaluate healthcare service performance using a multicriteriadecision-making approach based on patient perception data. This research employs a quantitative method, collecting data through structured questionnaires administered to 152 respondents. The instrument consists of 25 indicators derived from five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data validity and reliability were tested using Pearson correlation and Cronbach’s Alpha, confirming that the instrument is valid and reliable. Furthermore, data analysis was conducted using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method, including the construction of the decision matrix, normalization, optimization, and ranking. The results indicate that the reliability dimension achieved the highest preference value (A1 = 0.059), followed by empathy (A4) and tangibles (A5) (0.057), while responsiveness obtained the lowestvalue (A2 = 0.052). These findings demonstrate that reliability is the strongest aspect of healthcare service performance, whereas responsiveness requires priority improvement. This study contributes by providing an objective, systematic evaluation framework that integrates patient-perception-based service quality dimensions with the MOORA method to generate measurable performance rankings. The proposed framework offers a practical decision-support tool for healthcare managers in determiningpriority strategies for service quality improvement.